The commercial viability of direct powder rolled titanium: A systematic review and market analysis - Steytler, Megan (Centre for Materials Engineering, 2019)
Direct powder rolling (DPR) is thought to be a more cost-effective, more direct route to producing flat product of near final thickness. It is a particularly attractive route for titanium given that the existing wrought method of melting titanium sponge to ingot followed by rolling to slab to plate and finally to thin gauge product is an energy and capital-intensive process. There are several studies that have investigated the operational parameters of DPR, but there has been little assessment of the realization of DPR as a fully operational process producing a commercially viable product. The commercial viability of DPR is a particularly pertinent question for South Africa given the investment, by the Council for Scientific and Industrial Research and the Department of Science and Technology, in the development of an innovative powder manufacturing technology, as well as complementary powder metallurgy methods. A commercial viability assessment of DPR was structured around three analyses: 1.) whether a supply-side market exists to support a commercial enterprise, 2.) how the performance of DPR product compares to the performance of product produced via the conventional wrought route, and 3.) what range of potential product applications could be suitable for DPR product. A systematic review of published research was conducted by extracting and consolidating performance and process data, and a market analysis was conducted by sourcing price points from powder suppliers and wrought product suppliers. The performance of DPR product, in terms of elongation and ultimate tensile strength, was found to be comparable to the typical properties of ASTM grade 3 and 4 wrought product, which contain higher oxygen and are the least ductile of the commercially pure titanium grades. Due to the particulate nature of the starting stock and titanium’s affinity for oxygen, oxidation was found to be the single greatest problem in powder metallurgy. The upper and lower bounds of the oxygen range were identified, and the consolidation of data showed that an oxygen content of less than 0.2 wt% is not commonly achieved for non-hydride derived product. The possibility of producing a weldable product via DPR was found to be low, due to the unacceptable degree of chlorine content, which is typically greater than 0.02 wt% in low-cost (non-melt) commercially available powders, as well as the fact that weldability has not been reliably demonstrated for powder metallurgy product made from these powders. The existing powder market was also found to be inadequately geared towards supporting a commercial enterprise due to the small size of the market and the lack of availability of low-cost quality powders. The comparison of powder prices to wrought product prices showed that the potential for commercial viability is likely to exist only for thin gauge strip of less than 1mm thickness, as this is where cost savings can be attained through direct route processing. Based on the DPR product profile identified, the range of potential product applications was found to be greatly limited. The inability to reliably meet the typical properties of the “workhorse”, grade 2, excludes the largest proportion of applications for which pure titanium in strip form is used (heat exchangers and tubing). Furthermore, the lack of evidence of adequate weldability further restricts the usage of DPR product to applications where welding is not a critical requirement. For these reasons, it was concluded that DPR is not a commercially viable process.